Mapping 18F-fluorodeoxyglucose metabolism using PET/CT for the assessment of treatment response in non-small cell lung cancer patients undergoing epidermal growth factor receptor inhibitor treatment: a single-centre experience - Suppiah, Subapriya; Ahmad Saad, Fathinul Fikri; Mohad Azmi, Nur Hafizah; Nordin, Abdul Jalil (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2017)
Introduction: Specific mutations in the epidermal growth factor receptor (EGFR) characterize a subgroup of non-small cell lung cancer (NSCLC) patients that may be highly responsive to receptor inhibitor therapy. 18F-FDG PET/CT scans can map the glucose metabolism and treatment response of NSCLC. Therefore, we aimed to assess the pattern of metabolic response and outcome of inoperable NSCLC treated with epidermal growth factor receptor (EGFR) inhibitors, using 18F-FDG PET/CT scan. Methods: A retrospective study of inoperable NSCLC patients on EGFR inhibitor treatment that were referred for wholebody18F-FDG PET/CT scans was conducted based on cases scanned from January 2011 to June 2014. Comparison was made among serial attenuation-corrected fused PET/CT images for all study patients throughout the course of their treatment. Comparison based on PERCIST criteria was categorized into 4 levels ie. complete response (CMR), partial response (PMR), stable disease (SMD), progressive metabolic disease (PMD). Results: Overall, there were 5 patients identified, mean age: 57.4 years old +/- 2.9 years; The median survival time from initiation of EGFR inhibitor treatment to death was 17 months. Two patients showed initial partial metabolic response (PMR), two had progressive metabolic disease (PMD) and one had complete metabolic response (CMR) after the initiation of treatment. The patient with initial CMR had relapse and PMD 5 months later. Majority of patients eventually succumbed to their illness. Conclusions: Wholebody18F-FDG PET/CT is able to assess metabolic treatment response of NSCLC towards EGFR inhibitor treatment.